Comparison of different bile acid-phospholipid conjugates in acute hepatitis - Pathil-Warth, Anita; Warth, Arne; Chamulitrat, Walee; Stremmel, Wolfgang (European journal of clinical investigation, 2012)
Eur J Clin Invest 2011 Abstract Introduction The bile acid-phospholipid conjugate ursodeoxycholyl lysophosphatidylethanolamide (UDCA-LPE) is a promising novel compound with profound hepatoprotective functions in vitro and in vivo. Because of high costs of LPE synthesis from hydrolysis of phosphatidylethanolamide (PE), costs for UDCA-LPE synthesis for in vivo and human use can become quite high. In this study, we evaluated whether ursodeoxycholyl phosphatidylethanolamide (UDCA-PE), which is more cost-effective, could replace UDCA-LPE in terms of protection from hepatocellular injury. Materials and methods Anti-apoptotic and anti-inflammatory properties of UDCA-PE and UDCA-LPE were compared in TNFα/cyclohexamide (CHX)-treated HepG2 cells as well as in a mouse model of d-galactosamine/lipopolysaccharide (Gal/LPS)-induced acute liver injury. Results Ursodeoxycholyl lysophosphatidylethanolamide inhibited TNFα/CHX-induced apoptosis in HepG2 cells in a dose-dependent manner and markedly ameliorated Gal/LPS-mediated fulminant hepatitis in mice. In contrast, UDCA-PE showed weaker hepatoprotective functions at low concentrations, and protection was lost at higher dosage. Analysis of hepatic gene expression showed that both conjugates significantly reduced Gal/LPS-mediated expression of chemoattractants, such as monocyte chemotactic protein 1 (MCP1) and RANTES. These inhibitory effects by UDCA-PE were transient while those by UDCA-LPE were sustained in attenuating expression of inflammatory MCP1 and RANTES expression. Conclusions Our data underline the superiority of UDCA-LPE compared to UDCA-PE in ameliorating acute liver inflammation. This indicates the significance of the lyso-functional group of bile acid conjugate for optimal hepatoprotection and reduction in inflammation in vivo.
First published: 02 June 2011
Gesehen am 27.06.2018